Mapping nutrient adequacy for targeted policy interventions, with application to Uganda (2013/14) - Marivoet, Wim; Ulimwengu, John M. (International Food Policy Research Institute, 2018)
By opposing three sets of nutrient adequacy maps, this paper broadly identifies and locates the major bottlenecks behind Uganda’s micronutrient deficiency problems. Conform to the system approach currently advocated by researchers and development partners, these maps display the combined nutritional contribution of various food items while following a sequential logic from production to consumption. Using the latest round of Uganda’s National Panel Survey (2013/14), after reconversion from nutrients to food items, a spatially diverse set of policy responses are formulated. Despite significant heterogeneity across the country, our findings suggest that particular attention should be directed to increasing the national production and consumption of various beans, pulses and horticultural products such as carrots, dodo and mango, while focusing most efforts on the North East sub-region. Similarly, special attention must be devoted to sesame, given its current production level and its nutritional potential to address calcium, iron and zinc deficiencies.